Development and validation of a neonatal intensive care parent satisfaction instrument - Latour, Jos; Duivenvoorden, H.; Hazelzet, J.; Van Goudoever, J. (2012)
Objective: To develop and test the psychometric properties of the EMPATHIC-N (EMpowerment of PArents in THe Intensive Care-Neonatology) questionnaire measuring parent satisfaction. Design: A psychometric study testing the reliability and validity of a parent satisfaction questionnaire by applying confirmatory factor analysis including standardized factor loadings and subsequently Cronbach’s α reliability estimates across time, congruent validity, and nondifferential validity testing. Setting: A 30-bed neonatal intensive care unit in a university hospital. Patients: Two cohorts with a total of 441 parents whose child was admitted to the neonatal intensive care unit, January to December 2009. Interventions: None. Measurements and Main Results: In the first cohort, 220 of 339 (65%) parents responded; in the second cohort, 59 of 102 (58%) parents responded. Structural equation modeling and confirmatory factor analysis resulted in a sufficient model fit of 57 statements within five domains: Information, Care & Treatment, Organization, Parental Participation, and Professional Attitude. Standardized factor loading of these statements were between 0.58 and 0.91. Reliability measures, Cronbach’s α, of the domains ranged from 0.82 to 0.95. Reliability across time showed no evidence of statistically significant differences between the domains. Congruent validity was confirmed by a good correlation (p = .01) between the domains and four general satisfaction questions. Nondifferential validity showed no significant effect sizes between the infants’ characteristics and the domains, except between ventilated infants and parent participation statements and infants ≥30 wks gestational age and organizational statements. Conclusions: The EMPATHIC-N questionnaire is a valid quality performance indicator to measure the delivered care as perceived by parents.